Relationship between reduced folate carrier gene polymorphism and non-syndromic cleft lip and palate in Indian population. (February 2015) - Lakkakula, Bhaskar; Murthy, Jyotsna; Gurramkonda, Venkatesh Babu
Abstract Objective: Folate metabolism involves absorption, transport, modifications and interconversions of folates. The reduced folate carrier does not participate directly in folate metabolism but plays a major role in intracellular transport of metabolically active 5-methyltetrahydrofolate and maintains the intracellular concentrations of folate. The purpose of this study was to identify the prevalence of reduced folate carrier 1 (RFC1) A80G polymorphism and to further delineate its association with non-syndromic cleft lip and palate (NSCLP) in a south Indian population. Methods: In the present case-control study, we studied RFC1 gene A80G polymorphism to evaluate its impact on NSCLP risk in south Indian population. Blood samples of 142 cases with NSCLP and 141 controls were collected and genotyped using PCR-RFLP. Results: The genotype distribution in the control group followed Hardy–Weinberg equilibrium (p = 0.633). The G allele frequency of cases was 64.8% (184/284) and was significantly lower than that found in the control group 56.4% (160/282). The genotype distributions between NSCLP cases and controls was not significantly different (p = 0.131). The allelic model significantly increased the risk of NSCLP (G versus A; OR = 1.40; 95% CI: 1.00–1.97; p = 0.050). In subgroup analysis, the A80G variant showed significant association for the CLP group in dominant and allelic models. Conclusions: Altogether, our findings support the hypothesis that RFC1 A80G variant may contribute to NSCLP susceptibility in a south Indian population.